The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
Seventh IEEE International Symposium on Wearable Computers, 2003. Proceedings.
DOI: 10.1109/iswc.2003.1241386
|View full text |Cite
|
Sign up to set email alerts
|

MIThril 2003: applications and architecture

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(53 citation statements)
references
References 15 publications
(15 reference statements)
0
53
0
Order By: Relevance
“…A lot of studies on wearable computing system with complicated cables are reported [12,13]. Medical monitoring system is one of the most important applications of wearable computing systems.…”
Section: Related Work On Wearable Network Systemmentioning
confidence: 99%
“…A lot of studies on wearable computing system with complicated cables are reported [12,13]. Medical monitoring system is one of the most important applications of wearable computing systems.…”
Section: Related Work On Wearable Network Systemmentioning
confidence: 99%
“…MIThril: A Platform for Context-Aware Wearable Computing (www.media.mit.edu/wearables/mithril/) MIThril is a wearable research platform developed at the MIT Media Lab (DeVaul et al, 2001). Although not a commercial product, MIThril is indicative of the functionality that we can expect in nextgeneration wearable devices.…”
Section: Xybernaut Mobile Assistant ( W W W X Y B E R N a U T C Omentioning
confidence: 99%
“…Other techniques usually used are hidden Markov modelling (HMM) [12], artificial neural networks [13], and self-organizing maps [14]. However, the training and recognition procedures in DTW are potentially much simpler and faster.…”
Section: Dynamic Time Warpingmentioning
confidence: 99%